Peritoneal dialysis in children. Review of 8 years' experience. Issue 1 (January 1977) - Day, R E; White, R H
Abstract : During the years 1968-75, 59 periods of peritoneal dialysis were performed on 44 children aged from 2 days to 17 years. The commonest complication was peritoneal infection, which affected 68% of those under 2 years and 30% of older children. This was satisfactorily treated in all but one case which was due to Candida albicans. The use of combined intramuscular and intraperitoneal gentamicin therapy is described. 2 patients died as a result of massive intraperitoneal haemorrhage and one had a nonfatal intestinal perforation. In experienced hands peritoneal dialysis is a convenient, effective, and reasonably safe way of treating acute renal failure; it is best performed in centres capable of handling complex metabolic problems and investigating and treating the underlying renal disease.